Peran Strategi Kolaborasi, Influencer Marketing, dan Visual Branding Terhadap Keputusan Pembelian Produk Fashion Lokal Thanksinsomnia - Arlanda Muhammad Hakim; Amron Amron; Linda Ayu Oktoriza; Elia Resha Fatmawati (Pusat Riset dan Inovasi Nasional, 2026)
This quantitative study aims to analyze the role of collaboration strategies, influencer marketing, and visual brandingin influencing the purchase decision for the local fashion brand Thanksinsomnia. Primary data were collected from 158 respondents in Semarang City via online and offline questionnaires using a purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling (SEM) approach. The hypothesis testing results reveal that both collaboration strategies and visual branding exert a positive and significant influence on consumer purchasing decisions. Conversely, the influencer marketing variable was found to have no significant effect on purchasing decisions. The proposed research model demonstrates a remarkably high predictive capability in explaining the variation in the purchasing decision variable. This finding underscores that, within the context of a local fashion brand targeting Generation Z, strategic partnerships and a consistent visual identity are more dominant drivers than reliance on influencer-based promotions. The study contributes theoretically and offers practical recommendations for the local fashion industry to prioritize creative collaboration and authentic visual branding.